Link between eating disorders and depression - Muhammad Saleem; Sidra Sattar; Maryam Zafar; Rozmi Bin Ismail (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The present research sets out to gauge the interdependence between eating disorder risks (Dieting, Bulimia & Oral Control) and prevalence of depression among undergraduate students of higher learning institute of Pakistan (The Islamia University of Bahawalpur).After A-priori testing, 70 students from each faculty of respective university were recruited conveniently, and sample of three hundred fifty (N = 350) university students was taken. The total participants were equally divided into two categories of one seventy five (n = 175) for each gender. Two scales were employed to collect the data. First, Beck Depression Inventory (BDI-II) that is developed by Beck in 1996 with copy right® of Beck Corporation, and Second, Eating Attitude Test (EAT-26) evolved by© Garner et al. (1982) were employed. Reliability and Validity were found to be 0.82 and 100% respectively. Split-half reliability statistics, regression analysis, standard deviation, t-Test, and mean were employed to process the results. Overall findings of study depict that both eating disorder and depression are interdependent on each other. Conclusively, the level of depression in students of arts faculty was found higher than rest students of all four faculties. Furthermore, it was also found that female students are more vulnerable toward depression and eating disorder than male students of the Islamia University of Bahawalpur, Pakistan. This study would provide base line to youth researchers working in context of Pakistan. Limitations and suggestions are enclosed in the study.
Keywords: 330; eating disorder risks; depression; gender differences; university students; Pakistan